A contribuição do Programa Residência Pedagógica para a formação inicial do pedagogo: relato de uma residente - XAVIER, Débora Macedo (2022)
This course conclusion work aims to report experiences learned during the Pedagogical Residency Program (PRP) in an Early Childhood Education class at EMEF Prof. Antônio Gondim Lins, an internship field school located in the urban area of the municipality of Altamira/PA. Thus, from the immersion in the locus of the classroom, during the activities of Supervised Internship in Early Childhood Education, developed in parallel with the training actions of the PRP, I seek to reflect on how these integrated experiences contributed to my initial training, as a student/resident from the Pedagogy Course at the Federal University of Pará/Campus de Altamira. The methodology used was a qualitative approach, guided by the autobiographical narrative, supported by the record of my experiences in the setting process and conducting activities. The results made it possible for me to perceive that the supervised internship integrated to the actions of the PRP at this stage of teaching constituted a space for the construction of professional identity, insofar as they provided me with action-reflection-action on my initial training and experiences in real-time teaching, as a learner of the teaching profession and of the concreteness of pedagogical practice in Early Childhood Education, intertwined with theory-practice in the Higher Education Institution and in the Basic Education school, in addition to providing an opportunity to understand the specificities of the work of the teacher who at this stage of teaching.